The Gender Gap in Education in Eritrea in 1991-1998 : A Missed Opportunity? - Comenetz, Joshua; Brixiova, Zuzana; Bulir, Ales. (Washington, D.C. : International Monetary Fund, 2001)
This paper shows that during the 1990s, and before the 1998-2000 border war with Eritrea, the gender gap in education in Eritrea has widened on the national level, and large regional disparities have persisted. The gender gap appears to be linked to lower female teacher participation and limited employment opportunities. The widening of the gender gap is likely to have a long-term negative impact on both economic growth and poverty reduction.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet